STRATEGI MENINGKATKAN DATA SECURITY DALAM MEN JAGA PRIVASI PENGGUNA APLIKASI DAN LAYANAN ONLINE - Ayu Shintiya; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The presence of online applications and services has made it easier for users to interact and access information. However, its impact on user privacy is increasingly becoming a major concern, especially with increasing incidents of data leaks and privacy violations. Implementation of strong encryption, active monitoring of threats, and compliance with privacy regulations are effective strategies in improving data security and maintaining user privacy. Implementing this strategy requires collaboration between service providers, developers, and end users to create a more secure and trusted digital environment. Therefore, this research aims to identify and analyze effective strategies in improving data security to maintain user privacy in online applications and services. The research method used is a literature study to collect the latest information about data security challenges and strategies that can be implemented.